HAMBATAN AKSESIBILITAS FASILITAS OLAHRAGA DAN REKREASI BAGI WARGA BINAAN DISABILITAS FISIK DI LEMBAGA PEMASYARAKATAN - Subroto, Mitro; Prabowo, Riky Agus (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
This study investigates the barriers to accessibility of sports and recreational facilities for physically disabled inmates in correctional institutions. The urgency of this research stems from the need to promote inclusivity and well-being among vulnerable populations within the penal system. A qualitative approach was employed, utilizing interviews and observations to gather data from both inmates and facility staff. The findings reveal significant physical, structural, and attitudinal barriers that hinder access to these facilities, ultimately impacting the physical and mental health of disabled inmates. The study concludes that addressing these barriers is essential for fostering a more inclusive environment in correctional facilities, enhancing rehabilitation efforts and promoting the rights of disabled individuals.Keywords: accessibility barriers; sports facilities; disabled inmates; correctional institutions; rehabilitation.